2003
DOI: 10.1046/j.1365-8711.2003.06426.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodic flares in the methanol maser source G9.62+0.20E

Abstract: The class II methanol maser source G9.62+0.20E has been monitored since 1999 at 6.7 GHz and since 2000 at 12.2 GHz. Six flares have been observed to date. These flares are periodic, with an interval of 246 d between flares. The duration of the flare is approximately 3 months, with maximum amplitude reached a month after the start of the flare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 22 publications
4
80
0
Order By: Relevance
“…Various mechanisms can produce a change in magnetic field. It has been suggested that the periodic maser flares are caused by changes in the maser pumping resulting from a binary interaction between a massive protostar and companion (Goedhart et al 2003). Interactions between the magnetospheres of the two companions could cause a periodic behavior of the magnetic field, as has been observed in young low-mass binary systems (e.g., Massi et al 2008).…”
Section: Possible Origin Of the Observed Variabilitymentioning
confidence: 93%
“…Various mechanisms can produce a change in magnetic field. It has been suggested that the periodic maser flares are caused by changes in the maser pumping resulting from a binary interaction between a massive protostar and companion (Goedhart et al 2003). Interactions between the magnetospheres of the two companions could cause a periodic behavior of the magnetic field, as has been observed in young low-mass binary systems (e.g., Massi et al 2008).…”
Section: Possible Origin Of the Observed Variabilitymentioning
confidence: 93%
“…To date, periodic variations in the maser emission have been detected from a dozen HMYSOs (Goedhart, Gaylard & van der Walt 2003, 2004Goedhart et al 2009Goedhart et al , 2014Araya et al 2010;Fujisawa et al 2014). They are characterized either by flaring or sinusoidal patterns with periods ranging from 29.5 to 668 d and the relative amplitude from 0.2 to more than 30 (Fujisawa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…6.7 GHz methanol masers show a characteristic "periodic" flux variation, discovered by Goedhart et al (2003). The periodic variations have been detected in thirteen methanol maser sources so far, for which the observed period ranges between 30 and 668 days (Goedhart et al (2004(Goedhart et al ( ), 2009Araya et al (2010); Szymczak et al (2011);Fujisawa et al (2014); Maswanganye et al (2014)).…”
Section: Introductionmentioning
confidence: 93%